Whole-Exome Sequencing Reveals New Potential Mutations Genes for Primary Mucosa-Associated Lymphoid Tissue Lymphoma Arising From the Kidney - Wen, Shuang; Liu, Tianqing; Zhang, Hongshuo; Zhou, Xu; Jin, Huidan; Sun, Man; Yun, Zhifei; Luo, Hong; Ni, Ze; Zhao, Rui; Fan, Bo (Frontiers in Oncology, 2021)
Low-grade B cell lymphomas of mucosa-associated lymphoid tissue (MALT) lymphomas involving kidney was extremely rare, genetic alteration or molecular features was not yet explored, which may lead to limited the choices for postoperative adjuvant or targeted. Whole-exome sequencing based tumor mutation profiling was performed on the tumor sample from a 77-year-old female presenting with discomfort at the waist was pathological diagnosed as MALT lymphomas in the right kidney. We identified 101 somatic SNVs, and the majority of the identified SNVs were located in CDS and intronic regions. A total of 190 gain counts of CNVs with the total size as 488,744,073 was also investigated. After filtering with the CGC database, seven predisposing genes (ARID4A, COL2A1, FANCL, ABL2, HSP90AB1, FANCA and DIS3) were found in renal MALT specimen. Furthermore, we compared somatic variation with known driver genes and validated three mutational driver genes including ACSL3, PHOX2B and ADCY1. Sanger sequencing of germline DNA revealed the presence of a mutant base T of PHOX2B and a mutant base C of ADCY1 in the sequence, which were discovered for the first time in MALT lymphomas involving the kidney. Moreover, immunohistochemical analysis revealed that tumor cells were positive for CD20, CD79a, PAX5, CD21 and CD23, and expression of CD3, CD5 and CD8 were observed in reactive T lymphocytes surrounding tumor cells. These findings illustrated that concurrent aberrant PHOX2B and ADCY1 signaling may be a catastrophic event resulting in disease progression and inhibition of the putative driver mutations may be alternative adjuvant therapy for MALT lymphoma in the kidney which warrants further clinical investigation.